Ungkapan-Ungkapan Idiologis dalam Bahasa Kei - Robert Masreng (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Idioms is a culture of community product, it uses a language as its medium. This product uses language to express a goal or a meaning for its supporter community. Language uses as the mirror of language using for communication goal each other. Idioms to relate by that statement, this research focus in Kei language that indicates ideology it control its community in their life. This paper explains about (1) meaning, symbol that using and implemented on their community. The theory is use to analyze it is Danandjaja's theory and Spradley's theory. The research finds some idioms that have ideology meaning, with use symbols of thing and symbol of attitude. Using symbol in Kei's idioms can solve society problems on them. Its conclusions is verbal symbols and nonverbal symbols in Kei's ideologi idioms still alive and good care by its community.